Integrating Global Perspective Skills in Holistic Accounting Education: A Quantitative Analysis of Chinese Undergraduate Programs - Wangwei, Xuan; Singh, Simranjeet Kaur Judge AP Charanjeet (Journal of Posthumanism, 2024)
This study examines the integration of global perspective skills in holistic accounting education within Chinese undergraduate programs, emphasizing the impact of case-based learning on students’ preparedness for international accounting challenges. A mixed-methods approach was employed, analyzing survey data from 483 final-year accounting students and recent graduates across 12 Chinese universities alongside a curriculum review of selected programs. Multiple regression, ANCOVA, and structural equation modeling (SEM) revealed that global perspective skills significantly enhance holistic accounting education (β = 0.47, p < 0.001) and perceived international readiness. Students with high case-based learning exposure reported significantly greater global perspective skills (GPSS mean = 4.38, SD = 0.61) than those with low exposure (GPSS mean = 3.62, SD = 0.75; t(481) = 8.21, p < 0.001). Curriculum analysis indicated substantial variation in global perspective integration, with 67% of programs incorporating international case studies while 31% retained a localized focus. SEM results confirmed a strong mediating effect of case-based learning (indirect effect = 0.29, p < 0.01) on holistic accounting education and international preparedness. These findings highlight the need for standardized curriculum reforms, advocating for expanded use of international case studies, cross-border regulatory comparisons, and interdisciplinary approaches to better equip students for the evolving global accounting landscape.